2005
DOI: 10.1111/j.1439-0507.2004.01081.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tinea capitis in Ethiopian schoolchildren

Abstract: The prevalence of dermatophytosis and the spectrum of dermatophyte species were determined in children attending two schools in Addis Ababa, Ethiopia. Demographic and clinico-dermatological data were collected. Specimens were taken for microscopy and culture from all suspected lesions. Dermatophyte species were identified by morphology and biochemical tests, supplemented by sequencing of the rDNA ITS 2 region in selected isolates. From the Biruh Tesfa Elementary School (BTES) 824 students, and from Mount Olive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
5
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 29 publications
5
35
5
1
Order By: Relevance
“…Isolation rates ranging from 24%-93% have been reported in earlier studies from different geographical areas. (5,6,7) Our study showed KOH positivity rate of 42.2% among the clinically suspected cases, which was less compared with earlier studies by Jha BN et al and Woldeamanuel Y et al, where in the rates were 62.3% and 62% respectively; however, the KOH positivity rate was much higher when compared to 16.3% by Hogewoning AA et al (8,9,10) According to our study, the predominant age group affected was found to be 1-10 (56.86%). Similar findings have been noted in studies by A. G. Sajjan et al, Bose S. et al, Wani M.M.…”
Section: Discussioncontrasting
confidence: 56%
“…Isolation rates ranging from 24%-93% have been reported in earlier studies from different geographical areas. (5,6,7) Our study showed KOH positivity rate of 42.2% among the clinically suspected cases, which was less compared with earlier studies by Jha BN et al and Woldeamanuel Y et al, where in the rates were 62.3% and 62% respectively; however, the KOH positivity rate was much higher when compared to 16.3% by Hogewoning AA et al (8,9,10) According to our study, the predominant age group affected was found to be 1-10 (56.86%). Similar findings have been noted in studies by A. G. Sajjan et al, Bose S. et al, Wani M.M.…”
Section: Discussioncontrasting
confidence: 56%
“…By the 1970s to 1980s Trichophyton tonsurans, another anthropophilic dermatophyte, had become the most common cause of tinea capitis (21), and it now causes more than 95% of these infections in the United States (7). By contrast, species such as Trichophyton violaceum and Trichophyton soudanense, which are common causes of tinea capitis in parts of Africa and West Asia (5,15,24,25,35), have rarely been isolated from patients in the United States. Among 14,696 dermatophytes isolated from patients at 54 locations throughout the United States from 1985 through 1987, only 12 were identified as T. violaceum and only 2 were identified as T. soudanense (31).…”
mentioning
confidence: 99%
“…Infection rates for species that are endemic in other geographic regions can be equally impressive. Population surveys conducted in undeveloped and developing countries revealed clinical infection rates that never fell below one in five and often exceeded one in every two of the children sampled (3,6,13,14,15,19,20).…”
Section: Discussionmentioning
confidence: 99%